PENGARUH ARUS KAS OPERASI, PROFITABILITAS, KEBIJAKAN HUTANG DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM - Catur Puji Yanti; Murtanto Murtanto (EBID: Ekonomi Bisnis Digital, 2023)
This study aims to determine the effect of Operating Cash Flow, Profitability, Forest Policy and Dividend Policy on Stock Prices both simultaneously and partially, with the object of research being manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange (IDX). The sampling method for this study used the purposive sampling method with a total of 54 companies based on population and 20 companies were selected as samples. The design of this study is a causal study using quantitative methods and using secondary data. The data analysis technique uses a panel data regression technique, which combines cross section and time series data for 4 years from 2019-2022, using IBM SPSS software version 24.The results of this study partially show that Operating Cash Flow, Profitability, Debt Policy and Dividend Policy affect stock prices.